A review comparing deoxyribonucleoside triphosphate (dNTP) concentrations in the mitochondrial and cytoplasmic compartments of normal and transformed cells - Gandhi, Vishal V. (2011)
The deoxyribonucleoside triphosphate (dNTP) pools that support the replication of mitochondrial DNA are physically separated from the rest of the cell by the double membrane of the mitochondria. Perturbed homeostasis of mitochondrial dNTP pools is associated with a set of severe diseases collectively termed mitochondrial DNA depletion syndromes. The degree of interaction of the mitochondrial dNTP pools with the corresponding dNTP pools in the cytoplasm is currently not clear. We reviewed the literature on previously reported simultaneous measurements of mitochondrial and cytoplasmic deoxyribonucleoside triphosphate pools to investigate and quantify the extent of the influence of the cytoplasmic nucleotide metabolism on mitochondrial dNTP pools. We converted the reported measurements to concentrations creating a catalog of paired mitochondrial and cytoplasmic dNTP concentration measurements. Over experiments from multiple laboratories, dNTP concentrations in the mitochondria are highly correlated with dNTP concentrations in the cytoplasm in normal cells in culture (Pearson R = 0.79, p = 3 × 10(-7)) but not in transformed cells. For dTTP and dATP there was a strong linear relationship between the cytoplasmic and mitochondrial concentrations in normal cells. From this linear model we hypothesize that the salvage pathway within the mitochondrion is only capable of forming a concentration of approximately 2 μM of dTTP and dATP, and that higher concentrations require transport of deoxyribonucleotides from the cytoplasm.